Videothoracoscopy in Pleural Empyema Following Methicillin-Resistant Staphylococcus aureus (MRSA) Lung Infection - Duilio Divisi; Giovanna Imbriglio; Roberto Crisci (The Scientific World Journal)
Our study shows the different therapeutic procedures in 64 patients with pleural effusion due to MRSA pneumonia. The thoracostomy tube associated with pleural washing was decisive in 10 simple effusion patients. Video-assisted thoracic surgery allowed a complete resolution of the disease in 22 complex parapneumonic effusion patients. In 20 of 32 patients with frank pus in the pleural cavity, the videothoracoscopic insufflation of carbon dioxide (CO2) before thoracotomy facilitated the dissection of the lung tissue. In 12 patients, this approach was not applied because of cardiac insufficiency. Videothoracoscopy and decortication after thoracotomy ensured the recovery of functions.